2016
DOI: 10.6061/clinics/2016(03)03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life and risk of suicide

Abstract: OBJECTIVE:To identify the socio-demographic profiles, suicidal ideation, the presence of mental disorders and the quality of life of patients using mental health services in Arapiraca, Alagoas, Brazil.METHOD:Interviews were conducted in family health units and the Psychosocial Attention Center. The sample included 202 mental disorder patients with a risk of suicide attempts, 207 mental disorder patients without a risk of suicide attempts and 196 controls. This study used an identification questionnaire, the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
4
11
0
10
Order By: Relevance
“…A growing body of literature shows weaker handgrip strength to be associated with a lower physical quality of life, which in turn, is likely to stimulate suicidal thoughts. Indeed, previous studies have shown an association between suicidal ideation and poor quality of life in the adult population . On the other hand, those having suicidal thoughts might be likely to develop weaker handgrip strength, suicidal ideation may result in a decline in systemic physical functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature shows weaker handgrip strength to be associated with a lower physical quality of life, which in turn, is likely to stimulate suicidal thoughts. Indeed, previous studies have shown an association between suicidal ideation and poor quality of life in the adult population . On the other hand, those having suicidal thoughts might be likely to develop weaker handgrip strength, suicidal ideation may result in a decline in systemic physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown an association between suicidal ideation and poor quality of life in the adult population. 35,36 On the other hand, those having suicidal thoughts might be likely to develop weaker handgrip strength, suicidal ideation may result in a decline in systemic physical functioning. For example, one previous study found that higher muscular strength (highest 10th vs lowest 10th knee extension and handgrip) was associated with a 20%-30% lower risk of death from suicide in Swedish male adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, anxiety [ 31 ], sleep disorder [ 32 ], and other symptoms were also identified to contribute to risk of suicide. Quality of life was also significantly decreased in PD patients [ 33 ], which may bring mental problems including stigma, aloneness, and hopelessness [ 15 ], and all these could lead to an increased risk of suicide and/or suicidal ideation. It is important for clinical practitioners and caregivers to pay more attention to the mental status and risk of suicide in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating a clinical population, Alves Vde et al ( 19 ) found that patients who had a mental disorder and risk of suicide attempts had lower QoL than patients without the risk of suicide attempt. Further clinical studies found that patients diagnosed with depressive disorder ( 20 ), bipolar disorder ( 21 ), or epilepsy ( 22 ) and current suicidal ideation had worse QoL than patients with the same diagnoses and without suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%